Renewal Of Building Use Rights That Expire At The Malang Regency Land Office - Faya M., Bonick (International Significance of Notary, 2025)
ABSTRACT: Land registration aims to ensure legal certainty and certainty of land rights. With the implementation of land registration, the parties concerned can easily find out the status of the legal position of the particular land they face, its location, area and boundaries. The right to use buildings in the western legal sense before conversion comes from opstal rights stipulated in Article 71 of the Civil Code that "the right to ride a reef is a material right to own buildings, buildings and plantings on other people's yards. The method used to collect data from various literatures. This thesis research uses a qualitative approach. This research method is normative legal research or literature writing using a statutory approach (Statute Approach). The research location at the Malang Regency Land Office is on Jl. Kawi Canal No.10, Klojen District, Malang City, East Java 65116. Data collection techniques in library research are documentary techniques. Government Regulation Number 40 of 1996 states that renewal is submitted no later than 2 (two) years before the expiration of the Right to Use Building, which means that if it has passed 2 (two) years before the end of the Right to Build, the right holder cannot make a renewal of the Right to Use Building that he has. However, in PMNA / KBPN Number 9 of 1999, it is stated that it is submitted within a grace period of 2 (two) years which means that even though it has passed 2 (two) years before the Right to Build expires, the right holder can still apply for Renewal of the Right to Build.